Medidas de Protección en la Reproducción de la Violencia Económica y Patrimonial contra la Mujer del año 2020 y 2022 - Silva Bedoya, Juan Carlos (2023)
Few issues are as evident and little studied as it is, patrimonial and economic violence. The present study tries to demonstrate how economic or patrimonial violence is part of the cases of violence against women, in addition to physical, sexual, psychological, among others; however, this type of violence is less visible and therefore less attended to. Perhaps it is largely due to the fact that this type of violence is not reported. And it is not denounced, of course, because it is not punished fairly either. This, to the extent that there is no classification for this type of crime, although this type of violence is contemplated in the Comprehensive Organic Law to Prevent and Eradicate Violence against Women. This article explores the factors that prevent protection measures in cases of economic and patrimonial violence from effectively safeguarding the rights of women who suffer it, carrying out a qualitative analysis of the data collected. The investigative analysis proposes in the judgment, a modification to the procedure of equitable distribution of the profits generated in the family patrimony.